La Violencia and Changing Conflict on Antioquia’S Borderlands: The Northeast and Magdalena Medio Cases, 1948-1958 [la Violencia y Los Cambios de la Conflictividad en la Frontera Antioqueña: Los Casos del Nordeste y el Magdalena Medio, 1948-1958] - Henao-Holguin, D (Universidad de Antioquia, 2021)
This paper analyzes the Violencia phenomenon in Antioquia, Colombia during the period 1948-1958. It argues that even though this was a problem of multi-causal origin, the project of racial homogenization and social control that the local elite tried to deploy in the province became the most relevant factor of the conflict. Indeed, the background evidence gathered from both documentary and printed sources indicate that this project identified liberalism, especially Gaitanism, as the political manifestation of social and racial barbarism. In this context, Jorge Eliécer Gaitán’s death increased the bipartisan violence, which gained a growing annihilation character. © 2021 Universidad de Antioquia. All rights reserved.